Induced Abortions Among Women Having Undergone Total Hip Replacement: A Nationwide Register Study in Finland. (September 2019) - Kuitunen, I.; Skyttä, E. T.; Eskelinen, A.; Huhtala, H.; Artama, M.
Background and Aims: No previous studies have analyzed the connection between total hip replacement and induced abortion. We evaluated the nationwide induced abortion rates among women with and without total hip replacement. Materials and Methods: Data for this cohort study were gathered from national registers from 1987 to 2007. All fertile-aged (15–44 years old) females who had undergone primary total hip replacement in Finland were selected. The total hip replacement patient group comprised 1713 women and the reference group 5148 women. Information on all pregnancies for both groups before and after total hip replacement/index date was gathered from the medical birth register and the register of induced abortion. Logistic regression model was used to analyze the adjusted odds ratio for induced abortion. Adjustment was made for age at induced abortion, parity, previous induced abortions, previous deliveries, and marital status. Results: Women had higher induced abortion proportions after total hip replacement (17.9%) compared with women before total hip replacement (14.1%) and the referents (13.9%), but the differences were not statistically significant. Women in the total hip replacement patient group had significantly more induced abortions after total hip replacement due to maternal health issues (14.7%) compared with the referents (2.7%), p = 0.003. Patients in the total hip replacement group were not more likely to have their pregnancy ending in induced abortion than the women in the reference group (odds ratio 1.32, 95% confidence interval 0.89–1.96, p = 0.17). However, in the adjusted analysis, there was a trend for higher risk for pregnancy to end in induced abortion in the total hip replacement group in relation to the reference group (adjusted odds ratio 1.50 (confidence interval 0.99–2.28, p = 0.05). Conclusion: The total hip replacement patient group had higher, but statistically insignificant, induced abortion proportions compared with the reference group before and after the operation. After total hip replacement, the patients were not more likely to have a pregnancy ending in induced abortion. This finding remained statistically insignificant after adjusting with possible confounders.